Success factors for the management of recoverable solid residues at the Universidad Nacional de Costa Rica, Heredia, Costa Rica (Biocenosis, 2021)
Abstract:  A baseline study on technical aspects was conducted for the analysis of success factors in the management of recoverable solid residues at Universidad Nacional. Features were grouped into four areas: management planning, outreach and promotion, operation, and financing. A relative importance matrix concerning the elements involved in the institution's residues management was developed based on the results of the technical aspects study. The matrix showed that the sorting code, the use of media for disclosure, residue transportation, and income from the sale of materials are key elements in the process. The study also included self-assessment with an overall performance index above 87%. Additionally, an instrument was prepared to evaluate the knowledge, attitudes and barriers manifested by the university community regarding solid waste management, with no significant differences (p > 0.05) in the strata studied; therefore, the environmental education strategies designed could be applied to the three strata. In terms of knowledge, there is confusion regarding residue separation, which in turn becomes one of the main barriers, in addition to lack of time to invest in training activities. Finally, a valuation of externalities and an approximation of avoided costs showed how a scenario with a project of selective recollection has more favorable environmental impact, since the avoided costs can generate income, though not enough to make the system self-sustainable.
Keywords: attitude and barriers; environmental education; externalities; classification; university